2019
DOI: 10.1002/ece3.5470
|View full text |Cite
|
Sign up to set email alerts
|

Geographic variation in fitness‐related traits of the bladderwrack Fucus vesiculosus along the Baltic Sea‐North Sea salinity gradient

Abstract: In the course of the ongoing global intensification and diversification of human pressures, the study of variation patterns of biological traits along environmental gradients can provide relevant information on the performance of species under shifting conditions. The pronounced salinity gradient, co‐occurrence of multiple stressors, and accelerated rates of change make the Baltic Sea and its transition to North Sea a suitable region for this type of study. Focusing on the bladderwrack Fucus vesiculosus, one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 65 publications
(118 reference statements)
0
6
0
Order By: Relevance
“…Grazing pressure on particular macroalgal species may have changed not only due to the general decrease in mesograzer numbers but also to the restructuring of the mesograzer community, since the different consumer species differ with regard to their feeding preferences. Such preferences may (Nejrup et al 2012) or may not (Barboza et al 2019) differ among populations. The Kiel Bight population of F. vesiculosus is preferred over co-occurring A. vermiculophylla by the isopod I. balthica (Weinberger et al 2008), while A. vermiculophylla seems to be the preferred feed of the snail Littorina littorea relative to F. vesiculosus and F. serratus (C. Bommarito, GEOMAR, pers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Grazing pressure on particular macroalgal species may have changed not only due to the general decrease in mesograzer numbers but also to the restructuring of the mesograzer community, since the different consumer species differ with regard to their feeding preferences. Such preferences may (Nejrup et al 2012) or may not (Barboza et al 2019) differ among populations. The Kiel Bight population of F. vesiculosus is preferred over co-occurring A. vermiculophylla by the isopod I. balthica (Weinberger et al 2008), while A. vermiculophylla seems to be the preferred feed of the snail Littorina littorea relative to F. vesiculosus and F. serratus (C. Bommarito, GEOMAR, pers.…”
Section: Discussionmentioning
confidence: 99%
“…are among the most diverse and ecologically valuable (Kautsky et al 1992). These communities are exposed to increasing environmental stress in the course of global change (Werner et al 2016; Barboza et al 2019), as are many productive and diverse macroalgae‐based communities worldwide (Koch et al 2013; Wahl et al 2015b).…”
Section: Boxmentioning
confidence: 99%
See 1 more Smart Citation
“…In the specific case of the Baltic Sea, strong environmental gradients further exacerbate the definition of reference values. For example, Barboza et al (2019) showed how fitness-related traits of the habitat-forming macroalga Fucus vesiculosus vary in response to the prevailing salinity gradient as well as other local environmental drivers (e.g., loads of nutrients), potentially affecting the functioning of associated communities. Thus, in hard-bottom habitats of the Baltic Sea, the analysis of the main processes shaping the structure of communities and functioning is especially important to disentangle natural drivers of biodiversity from factors caused by human activities.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, both Atlantic and Baltic Sea populations are locally adapted to salinity; a reciprocal transplant experiment in a common garden found that populations grew better in their local salinity compared to the foreign salinity (24 and 4 PSU, respectively [28];). Despite such adaptation the Baltic Sea salinity gradient remains as a major factor affecting size, morphology and chemical contents of F. vesiculosus [29].…”
Section: Introductionmentioning
confidence: 99%